Laboratory Investigation on Key Technological Parameters of Brick Concrete Recycled Coarse Aggregate Strengthened by Negative Pressure - Liu, Hongzhe; Zhao, Zhizhong; Yang, Zhenyu; Wang, Risheng; Xu, Meng (Frontiers in Materials, 2022)
The strengthening application of brick concrete recycled coarse aggregate (BCRCA) has become a “troublesome issue,” so in-depth research on the strengthening method of BCRCA is needed. In order to improve the strengthening effect of BCRCA and bring out the large-scale application of brick concrete waste, the strengthening method of brick concrete recycled coarse aggregate should be studied. Firstly, the overall key performance parameters of BCRCA were compared and analyzed. Then the microstructure of BCRCA was tested by CT scanning technology to study the internal pore space and its distribution characteristics. Finally, the performance of BCRCA was strengthened by negative pressure, and the influence of key parameters such as negative pressure, pressurization time, pressurization temperature, and mixing frequency on the strengthening effect was investigated in this process. The test results show that the apparent density of brick mix coarse aggregate is about 8% lower than that of limestone coarse aggregate, the water absorption rate is more than 5 times higher, and the crushing value is about 2.5 times. The reason for this phenomenon is the presence of 30%-40% brick in the brick mix coarse aggregate, which is mainly made of clay sintering, with more pores and uneven distribution. In the process of applying negative pressure, the infusion of cement slurry can significantly improve the crushing value, water absorption rate, and surface density index of brick mix coarse aggregate. With the increase of cement slurry infusion, the strengthening effect is better. When the applied pressure value is -70 KPa, the pressurization time is 12 min, and the temperature is 70℃, the best reinforcement effect can be obtained by the second mixing of brick mix coarse aggregate.